Photocatalytic-oxidation and photo-persulfate-oxidation of sulfadiazine in a laboratory-scale reactor: Analysis of catalyst support, oxidant dosage, removal-rate and degradation pathway. (15th September 2018) - Yadav, M S Priyanka; Neghi, N.; Kumar, Mathava; Varghese, George K.
Abstract: The extent of sulfadiazine (SDZ) removal via photo-degradation (UV-C), photocatalysis with TiO2 (UV-C/TiO2 ) and photo-persulfate-oxidation (UV-C/PS) was investigated in a batch reactor under different UV-C power levels (i.e. 14, 28, 42 and 56 W). Moreover, effects of suspended/immobilized catalyst, i.e. TiO2 slurry/TiO2 supported on granular activated carbon (GAC-TiO2 ), on SDZ removal and corresponding SDZ degradation kinetics under different catalyst loading (1–6 g/L) were explored. Around 41.7% SDZ removal was observed after 120 min in UV-C system at the highest power level, i.e. 56 W. On the other hand, photocatalysis with TiO2 and GAC-TiO2 has shown better SDZ removal than photo-degradation. In UV-C/TiO2 (4 g/L and 28 W) and UV-C/GAC-TiO2 (5 g/L and 28 W) systems, SDZ removals were 91.8% after 120 min and 100% after 60 min, respectively; however, TOC analysis has revealed that 45.4% and 60.8% SDZ was mineralized in these systems, respectively. In UV-C/PS system, near complete degradation of SDZ (99.8%) was observed within 10 min under 50 mg/L of PS and 28 W UV illumination. On the other hand, complete SDZ removal was observed in PS alone system at a dosage of 1000 mg/L but the formation of S O 4 2 − was found to be a drawback. In photolysis and photocatalysis systems, SDZ removal followed pseudo-first-order kinetics whereas the kinetics followed pseudo-second-order in UV-C/PS system. The comparison of electrical energy consumed (EEO ) in different systems revealed that UV-C/GAC-TiO2 and UV-C/PS system were energy efficient compared with other systems. The LC-MS analysis has confirmed the cleavage of C-N bonds in the pyrimidine ring followed by S-N bonds in the sulfonyl group, which was found to be the major degradation pathway of SDZ. Graphical abstract: Image 1 Highlights: Photocatalytic SDZ removal was remarkable using GAC-TiO2 than with nano-TiO2 . SDZ was completely mineralized in UV-C/PS system. SDZ removal in UV-C/PS system was fitted well with pseudo-second-order kinetics. System performance was evaluated using electrical-energy consumed per-order concept. UV-C/PS was 536 and 80 times lesser energy consuming compared to UV-C and UV-C/TiO2 .